Textual Criticism of Hadith in Contemporary Islamic Thought: a Comparative Analysis of Salafi and Sufi Approaches - Nur Muhammad Anas Mohd Razak (Al-Bayān, 2025)
The clash between Salafi and Sufi schools of thought has shaped academic discourse and religious practice among Muslims worldwide. Therefore, this study examines the methodology of matn criticism developed by Ibn al-Qayyim from the Salafi tradition and Mullā al-Qārī from the Sufi tradition. The research employs a qualitative design, with data analyzed inductively, emphasizing critical editions of texts alongside textual and comparative methods. The findings reveal that both scholars share three out of four fundamental principles in matn criticism: contradiction with the Qurʾān, contradiction with authentic hadith, and the attribution of expressions unbefitting of the Prophet. However, they differ on the principle of contradiction with reason. This study brings positive implications by proposing an integrative framework that combines the Salafi tradition’s textual approach with the Sufi tradition’s contextual sensitivity, strengthening the preservation of hadith authenticity against unverified narrations.